Paradoxes of Business: Towards A Practice Model to Attend to Paradox Tensions in Organizations and Develop the Leaders of Tomorrow (International Journal of Applied Research in Management and Economics, 2020)
Paradoxes in business i.e. strategy paradoxes, leadership paradoxes, management and organizational paradoxes are inseparable from organizations’ front-end decision making. Existing literature has examined these paradoxes in mainly diverse theory driven perspectives that pointed towards the need to develop a learning cycle to sustain a practical model to help in navigating the business paradoxes. The aim of this paper is to uncover the best possible practical approach that would facilitate the process of navigating the paradoxes in organizations. I review a vast array of paradox and brain plasticity literature and conclude that a change in leadership behaviour towards accepting, embracing, and exercising these paradoxes in a form of a business simulation is crucial. Thus, I propose a learning model to sustain and support this practical model.